Therapeutic Targeting of Autophagy in Pancreatic Ductal Adenocarcinoma - Raufi, Alexander G.; Liguori, Nicholas R.; Carlsen, Lindsey; Parker, Cassandra; Hernandez Borrero, Liz; Zhang, Shengliang; Tian, Xiaobing; Louie, Anna; Zhou, Lanlan; Seyhan, Attila A.; El-Deiry, Wafik S. (Frontiers in Pharmacology, 2021)
Pancreatic ductal adenocarcinoma (PDAC) is an aggressive disease characterized by early metastasis, late detection, and poor prognosis. Progress towards effective therapy has been slow despite significant efforts. Novel treatment approaches are desperately needed and autophagy, an evolutionary conserved process through which proteins and organelles are recycled for use as alternative energy sources, may represent one such target. Although incompletely understood, there is growing evidence suggesting that autophagy may play a role in PDAC carcinogenesis, metastasis, and survival. Early clinical trials involving autophagy inhibiting agents, either alone or in combination with chemotherapy, have been disappointing. Recently, evidence has demonstrated synergy between the MAPK pathway and autophagy inhibitors in PDAC, suggesting a promising therapeutic intervention. In addition, novel agents, such as ONC212, have preclinical activity in pancreatic cancer, in part through autophagy inhibition. We discuss autophagy in PDAC tumorigenesis, metabolism, modulation of the immune response, and preclinical and clinical data with selected autophagy modulators as therapeutics.